Polymer-stabilized ruthenium nanoparticles as the catalysts of selective D-glucose oxidation. - L. Zh. Nikoshvili; V. Yu. Doluda; E. M. Sulman (Тонкие химические технологии)
Physicochemical and catalytic properties of Ru nanoparticles stabilized in HPS matrix were investigated. Ru nanoparticles with diameter of 1.2 nm, which reveal high stability, activity and selectivity (up to 99.8% at 99.5% conversion) in reaction of D-glucose oxidation, are obtained.